1976
DOI: 10.1021/es60112a005
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric oxidation of chlorinated ethylenes

Abstract: Limestone Slurry Scrubbing. Stack gas is washed with a recirculating slurry (pH of 5.8-6.4) of limestone and reacted calcium salts in water using a two-stage scrubber system for particulates and SO2 removal. Limestone feed is wet ground prior to addition to the scrubber effluent hold tank. Calcium sulfite and sulfate salts are withdrawn to a disposal area for discard.Lime Slurry Scrubbing. Stack gas is washed with a recirculating slurry (pH of 6.0-8.0) of calcined limestone (lime) and reacted calcium salts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 10 publications
1
55
0
Order By: Relevance
“…Hypothetical mechanisms for TCA formation have been suggested using perchloroethene as a starting material [12,13]. 1,1,2-Trichloroethene is not considered a precursor because laboratory studies of the simulated atmospheric degradation have shown neither the formation of TCA nor the formation of the TCA precursor trichloroacetylchloride [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hypothetical mechanisms for TCA formation have been suggested using perchloroethene as a starting material [12,13]. 1,1,2-Trichloroethene is not considered a precursor because laboratory studies of the simulated atmospheric degradation have shown neither the formation of TCA nor the formation of the TCA precursor trichloroacetylchloride [14].…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed discussion of the optical system, interferometer, and spectral data techniques are given elsewhere. 2 In these experiments the path length was 144 m and spectral resolution was 1.0 cm" 1 .…”
Section: Methodsmentioning
confidence: 99%
“…30 Subsequent measurements of the reaction products of photooxidation in the presence of nitrogen oxide indicated dichloroacetyl chloride was a major product with smaller yields of formic acid and phosgene. 31 Dichloroacetyl chloride is reported to be an eye irritant. 32 No formaldehyde, acrolein, or peroxyacyl nitrates were detected.…”
Section: Relating Parameters Of Eye Irritation To Ambient Responsementioning
confidence: 99%
“…32 No formaldehyde, acrolein, or peroxyacyl nitrates were detected. 31 Laboratory reaction studies with simple mixtures indicate the peroxynitric acid is likely to be a significant product in atmospheric photochemical reactions. 33 - 34 The structure of peroxynitric acid, HO2 NO2 is similar to several other eye irritants so it too may contribute to the intensity of eye irritation observed in ambient atmospheres.…”
Section: Relating Parameters Of Eye Irritation To Ambient Responsementioning
confidence: 99%